Implications of Financial Understanding and Attitude in The Context of Financial Management MSMEs - Nadiyani, Putri; Lubis, Kartika Sari (Universitas Batanghari, 2024)
The purpose of this study is to find out how the attitudes and knowledge of MSMEs about money influence the financial management practices of MSMEs. The result show that financial knowledge has a substantial impact on financial management behavior. This is supported by the t-statistic value of 4.626> t table value of 1.679 and p-value of 0.000 <0.05, which show that a person's level of financial education improves the behavior they use for money management. The successful achievement of a t-statistic value of 3.363>t table value 1.679 and a p-value of 0.001 <0.05 indicates a strong association between financial attitudes and financial management behavior. The coefficient of determination test findings indicate that there is a 47.4%, or 0.474, influence of financial attitudes (X2) and financial knowledge (X1) on financial management behavior (Y). This research offers an insightful new viewpoint and fully and completely demonstrates the influence of financial attitudes and awareness of the behaviors associated with financial management.